Grenada : Statistical Appendix. (IMF Staff Country Reports; Country Report, 2000)
The statistical data on the GDP, output and prices of major agricultural crops, consumer price index, summary finances of the central government, central government revenue and grants, and central government expenditure of Grenada are presented. The data on operations of the national insurance scheme, consolidated accounts of the banking system, operations of the eastern Caribbean central bank in Grenada, consolidated accounts of the commercial banks, summary balance of payments, merchandise exports, direction of trade, and related economic indices are also presented.